The Singapore Tuberculosis Elimination Programme: the first five years - Chee Cynthia B.E; James Lyn (The World Health Organization, 2003)
The Singapore Tuberculosis Elimination Programme (STEP) was launched in 1997 because the incidence of the disease had remained between 49 and 56 per 100 000 resident population for the preceding 10 years. STEP involves the following key interventions: directly observed therapy (DOT) in public primary health care clinics; monitoring of treatment progress and outcome for all cases by means of a National Treatment Surveillance Registry; and preventive therapy for recently infected close contacts of infectious tuberculosis cases. Among other activities are the revamping of the National Tuberculosis Notification Registry, the discontinuation of BCG revaccination for schoolchildren, the tightening up of defaulter tracing, and the education of the medical community and the public. Future plans include an outreach programme for specific groups of patients who are unable to attend their nearest public primary care clinics for DOT, the detention of infectious recalcitrant defaulters for treatment under the Infectious Diseases Act, the molecular fingerprinting of tuberculosis isolates, and targeted screening of high-risk groups. The incidence of tuberculosis fell from 57 per 100 000 population in 1998 to 48 per 100 000 in 1999 and continued to decline to 44 per 100 000 in 2001. With political will and commitment and the support of the medical community and the public it is hoped that STEP will achieve further progress towards the elimination of tuberculosis in Singapore.